Religion, culture, and cancer: insights from a qualitative study on coping experiences of Filipino patients - Ahmadi, Fereshteh; Zandi, Saeid; Poblete, Mae-Lanie (Frontiers in Psychology, 2024)
Introduction Meaning-making coping is used by people with cancer to help them deal with the stress and emotional turmoil associated with their diagnosis. It is a multifaceted approach that can be influenced by cultural, existential, and personal factors. Research on meaning-making coping among Filipinos diagnosed with cancer is sparse. This study examines how a sample of Filipino people with cancer cope with their illnesses. Methods We employed a qualitative approach. The study involved 20 participants with various types of cancer in the Philippines who were selected through purposive sampling and agreed to be interviewed. Results The thematic analysis of the interviews revealed the application of both religious and secular meaning-making coping by participants. The study also confirmed the potential influence of culture on coping strategies. Discussion The results indicate that religion plays a significant role in Filipino coping mechanisms, given that the Philippines is predominantly a Christian nation. Additionally, the findings highlight the importance of close family ties in Filipino culture and how it contributes to coping with cancer.